Knowledge and attitudes of health-based students in a public university in Malaysia on hepatitis B infection - Sheikh Zainal Abidin, Siti Nurafifah; A. Rahman, Nor Azlina; Haque, Mainul (Cukurova University |, 2019)
Purpose: This study was intended to assess the knowledge and attitude of health-based students regarding HBV infection, its associated factors and the relationship between the knowledge and attitude. Materials and Methods: This study was a cross-sectional study. The data had been collected from the students selected through convenience sampling in a public university in Malaysia using a self-administered questionnaire. Results: Among the 117 student respondents, nearing half (44.4%) had adequate knowledge related to HBV infection and nearing fourth-fifth (78.6%) had attitude score of satisfactory level. Genders and community status showed no association with knowledge and attitude regarding HBV infection, while faculty was significantly associated with both knowledge and attitude. Only knowledge but not attitude was found to have significant positive correlation with age and year of study. Knowledge was also found to be positively correlated with attitude regarding HBV infection. Conclusion: This research found that age and year of study were only positively correlated with knowledge regarding HBV, but not attitude. Besides, the result showed significant positive correlation between knowledge and attitude regarding HBV infection, meaning higher knowledge was associated with higher attitude.